2023
DOI: 10.29333/iji.2023.16259a
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Teaching Presence on Students’ Motivation and Performance in A Long-term Online Gamified EFL Listening Course

Abstract: Studies have proven that gamification in learning can increase motivation and engagement, however, since the pandemic broke out and instruction was held fully online for a long time, its effectiveness has been under question. The motivation was also reportedly decreased in long-term gamified classes. Nonetheless, in gamification research, teaching presence (TP) as the predictor of success in distance instruction has not adequately been included. The study investigated the effects of TP on students' motivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…From the data obtained as a result of the research, it was observed that the game-based museum activities were effective in increasing the achievement and attitude levels of the experimental group students towards the Visual Arts Lesson, in which they were applied in the Ankara State Painting and Sculpture Museum. In addition to these, a study by Suharno, Suherdi and Gunawan (2023) explored the effects of Gamified EFL listening course as well as the motivation aspect. Similarly Assapun & Thummaphan (2023) investigated the effectiveness board game based learning fostering problem solving competency and found a positive high engagement.…”
Section: Game-based Learning / Gamificationmentioning
confidence: 99%
“…From the data obtained as a result of the research, it was observed that the game-based museum activities were effective in increasing the achievement and attitude levels of the experimental group students towards the Visual Arts Lesson, in which they were applied in the Ankara State Painting and Sculpture Museum. In addition to these, a study by Suharno, Suherdi and Gunawan (2023) explored the effects of Gamified EFL listening course as well as the motivation aspect. Similarly Assapun & Thummaphan (2023) investigated the effectiveness board game based learning fostering problem solving competency and found a positive high engagement.…”
Section: Game-based Learning / Gamificationmentioning
confidence: 99%
“…So, mindfulness helps individuals to be aware and gets rid of accidental thoughts and abnormal behavior, and be able to regulate their behavior (Bajaj et al, 2016). Several studies con rmed the reduction of stress through mindfulness meditation and also emphasized feeling good (e.g., Cahn & Polich, 2006;Lawlor, 2005;Ludwig & Kabat-Zinn, 2008;Siegel, 2007Siegel, , 2010Speca et al, 2000;Suharno et al, 2023). Mindfulness promotes inventiveness, adaptability, and information utilization in addition to memory and retention.…”
Section: Introductionmentioning
confidence: 99%